Analysis of marketing strategies in civil engineering in cariri Ceará: a study based on construction companies and followers of the social network Instagram - Saraiva, Ingra Maria Ferreira; Silva Neto, Dimas de Castro e (Brazilian Journal of Production Engineering, 2024)
Analyzing followers’ profiles on social media is crucial for the digital marketing of civil engineering companies. This study investigated digital marketing strategies in construction companies in the Cariri region of Ceará, divided into two parts. The Instagram user profile of a local construction company was analyzed and marketing methods were compared with other companies in the region. Specific objectives included evaluating demographic and geographic segmentation, identifying the company’s digital presence, and assessing the feasibility of digital marketing. The methodology involved literature review, Instagram data analysis, and a survey applied to local construction companies. Results indicated increased engagement and reach for the studied construction company, with over a 10% difference between male and female users, and the majority of followers in the 25 to 34 age group. Most construction companies use Instagram as their main social network, but many do not employ specialized professionals, facing challenges such as lack of time and knowledge in marketing tools. The research highlights the evolution of marketing in the studied construction company and users’ preference for short video content.